A Study of Engaging Audiences and Driving Brand Success-Social Media Strategies at Hungama Digital Media Entertainment - Pawar, Khushal (ATLAS SkillTech University, 2025)
This internship report, "A Study of Engaging Audiences and Driving Brand Success - Social Media Strategies at Hungama Digital Media Entertainment," presents a detailed account of my valuable experience as a Social Media Marketing intern at Hungama Digital Media. This internship was part of my second-year MBA curriculum at Atlas SkillTech University and was guided by Prof. Ameya Ambulkar. Throughout the internship, I contributed to several social media marketing initiatives, including content creation, campaign management, and audience engagement strategies. This report synthesizes key insights and practical knowledge, emphasizing my contribution to increasing brand awareness, enhancing customer engagement, and driving overall business performance. Social media marketing in today’s digital landscape plays a crucial role, and this report reflects how my internship experience helped develop the skills necessary to implement impactful strategies. The executive summary provides an overview of the report’s detailed findings and reflections, offering readers a comprehensive understanding of the transformative experience at Hungama Digital Media.
Project Report on A Study of Engaging Audiences and Driving Brand Success-Social Media Strategies at Hungama Digital Media Entertainment (2023-2025) Under the Guidance of Prof. Sadaf Hashmi
Keywords: Digital Media Entertainment; Social Media Marketing; campaign management; Digital Media; digital landscape